Surveying Profession in Nigeria: Stimulating interest and encouraging youth participation for future sustainability - Matori, A.N (2012)
As the most populous country in Africa and one of the most populous in the world, Nigeria is a potentially huge market for surveying services. However, the Surveying profession in Nigeria appears to be witnessing a gradual but steady decline in the quantity and quality of people practicing it. Young surveyors are abandoning the profession and high-school graduates do not seem motivated to enroll for the course in higher educational institutions. This paper provides updated insights into the challenges faced by practicing surveyors and potential surveyors in the country. Reasons why the profession does not rank among top choices for high-school graduates poised for tertiary education are discussed. Furthermore, core factors militating against the development of the profession and its practitioners are outlined and possible practical solutions to these problems are proffered.